Biologically active and health promoting food components of nuts, oilseeds, fruits, vegetables, cereals, and legumes - Albuquerque, T.G. (2021)
The primary role of diet is to provide, in quality and quantity, enough nutrients to meet basic metabolic requirements of consumers. Cereals, legumes, vegetables, fruits, nuts, vegetable oils, and related products are daily consumed by worldwide population as fundamental source of food energy, but also due to its richness in biologically active compounds with potential health promoting properties. There are thousands of bioactive compounds already identified and studied for their health promoting properties, however there still a lot of research to be done. This chapter describes the main food sources, as well as, health promoting properties, of some food components (phytosterols, fatty acids, polyphenols, carotenoids, glucosinolates, dietary fiber, isoflavones, and lignans). In fact, these compounds were selected due to its abundance in some of the major consumed food groups. Nuts, oilseeds, and derived products are well known for their richness in phytosterols and unsaturated fatty acids. In the last years, great attention has been given to this group of compounds because they are linked with several health benefits, namely antiinflammatory, antioxidative, anticarcinogenic activities, and cholesterol lowering capacity. On the other hand, fresh fruit and vegetables are the major sources of polyphenols, carotenoids, and glucosinolates. Nutritional guidelines promote the consumption of three to five daily servings of fruits and vegetables for protection against chronic diseases, such as cardio and neurovascular diseases. These foods, besides providing basic nutrition confers other significant health effects mainly due to its content in vitamins (especially vitamins C and A) minerals, polyphenols, and soluble and insoluble fiber. Lastly, cereals and/or legumes are the major sources of dietary fiber, lignans, and isoflavones. Besides their nutritional role, several scientific and epidemiological studies have shown that regular consumption of cereals and/or legumes and their related products are associated with reduced risk of various types of chronic diseases as cardiovascular diseases, type 2 diabetes, and obesity, and some types of cancers as colorectal, prostate, breast, and estrogen-related cancers. These evidences can mean that regular consumption of cereals and legumes promote human health and consequent prevention of diseases.